Population Dynamics of Horse Mackerel (Trachurus Mediterraneus Ponticus) in the Bulgarian Black Sea Coast. (19th March 2013) - Yankova, Maria
Abstract : The horse mackerel Trachurus mediterraneus is a commercially important pelagic fish species in the Black Sea fishery. The present investigation was carried out between May and December 2010 along the Bulgarian coast of the Black Sea. Population parameters of horse mackerel from the trawl and fishing nets catches were estimated from length frequency data, by using ELEFAN-I computer program. The ELEFAN-I analysis gave the following Von Bertalanffy Growth Function (VBGF) parameters: the asymptotic length ( L ∞ ) = 19.95  cm, growth coefficient value was k = 0.640, and the hypothetical age at which length is zero was t 0 = − 0.548 . Based on these growth parameters, the total mortality coefficient (Z ) during the study period was estimated to be 2.99. The estimated value for natural mortality (M ) was 1.08; hence, the fishing mortality coefficient (F ) was 1.91. The estimated value for the exploitation rate (E ) using the length converted catch curve was 0.64. The estimated sizes of T. mediterraneus at 25, 50, and 75 percent probabilities of capture were 16.80 cm, 18.72 cm, and 20.64 cm, respectively.